Effect of Polarization on Cross-Spectral Density Matrix - Gautam A.; Naik D.N.; Narayanamurthy C.S.; Singh R.K. (My University, 2025)
Coherence-polarization properties of different beams are experimentally measured in the far-field from the source and results are presented for incoherent sources with three different polarization features, such as unpolarized, diagonally polarized, and spatially depolarized. These results highlight the role of polarization tailoring on far-field coherence-polarization properties of the incoherent vector source. The effect of polarization on far-field coherence is analyzed using a beam cross-spectral density (CSD) matrix, and the role of polarization tailoring on the CSD matrix is demonstrated. Two-dimensional spatial distributions of all four elements of the CSD matrix are experimentally realized using a field-based interferometer with Sagnac geometry in combination with a four-step phase-shifting technique. © 2024 by the authors.